2007
DOI: 10.1093/ajcn/85.2.474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the maternal βE-globin gene on hematologic responses to iron supplementation during pregnancy

Abstract: Background: It is customary in Southeast Asia to treat pregnant anemic women with iron supplements, but anemia in this region may be complicated by thalassemia and hemoglobinopathies, which lead to an ineffective response. Objective: The aim was to determine whether routine iron supplementation during pregnancy in this area, which has a high prevalence of thalassemia and hemoglobinopathies, is an effective control strategy for iron deficiency anemia. Design: A prospective study was conducted. Seventy-six pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Thus, both ferritin and sTfR are affected by IHbD and, therefore, do not reflect Fe status alone. This is in agreement with previous findings that different types of IHbD respond differently to Fe supplementation (35) , and it has been shown that hepcidin concentrations and Fe absorption differ by IHbD type (13,14) .…”
Section: Discussionsupporting
confidence: 93%
“…Thus, both ferritin and sTfR are affected by IHbD and, therefore, do not reflect Fe status alone. This is in agreement with previous findings that different types of IHbD respond differently to Fe supplementation (35) , and it has been shown that hepcidin concentrations and Fe absorption differ by IHbD type (13,14) .…”
Section: Discussionsupporting
confidence: 93%
“…However, the individuals tested had been derived from a population in Bangkok and not from a population of the Northeast of the country, where anemia and iron deficiency are common and Thalassemia is a public health problem [30,31]. Haemoglobin E (Hb E) is the most common trait for hemoglobinopathies prevalent in the Northeast of Thailand [32]. Adjusted HbA1c values were higher in a group of Asians in comparison to white individuals with Impaired Glucose Tolerance (IGT) but the adjusted HbA1c difference was insignificant (5.78% versus 6% respectively) [29].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, supplementation to pregnant women with hemoglobulin E heterozygote or homozygote states did not seem to cause iron overload. 55 Hemoglobinopathies contribute considerably but variably to the burden of anemia, potentially distorting estimates of the prevalence of IDA. 54 For example, in Thailand, hemoglobinopathy was found to be a greater contributor to anemia than iron deficiency in schoolchildren and pregnant women, 56,57 whereas in rural Indian children, hemoglobinopathy was only a minor contributor.…”
Section: Iron Overloadmentioning
confidence: 99%